2010
DOI: 10.1002/jbmr.212
|View full text |Cite
|
Sign up to set email alerts
|

Odanacatib in the treatment of postmenopausal women with low bone mineral density: Three-year continued therapy and resolution of effect

Abstract: The selective cathepsin K inhibitor odanacatib (ODN) progressively increased bone mineral density (BMD) and decreased boneresorption markers during 2 years of treatment in postmenopausal women with low BMD. A 1-year extension study further assessed ODN efficacy and safety and the effects of discontinuing therapy. In the base study, postmenopausal women with BMD T-scores between À2.0 and À3.5 at the lumbar spine or femur received placebo or ODN 3, 10, 25, or 50 mg weekly. After 2 years, patients (n ¼ 189) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
148
0
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 229 publications
(163 citation statements)
references
References 23 publications
7
148
0
8
Order By: Relevance
“…A similar pattern was also observed with odanacatib, a selective cathepsin K inhibitor, in a 2-year study in which a transient rise in BTMs above baseline after treatment discontinuation was seen. (76) The implication of this rebound effect on the clinical outcomes is not clear.…”
Section: Safety Of Bisphosphonatesmentioning
confidence: 99%
“…A similar pattern was also observed with odanacatib, a selective cathepsin K inhibitor, in a 2-year study in which a transient rise in BTMs above baseline after treatment discontinuation was seen. (76) The implication of this rebound effect on the clinical outcomes is not clear.…”
Section: Safety Of Bisphosphonatesmentioning
confidence: 99%
“…The odanacatib resolution-of-effect study reported by Eisman and colleagues (6) is well designed, and the results are interesting, but several important limitations are worth noting. The most important shortcomings of the study are the small sample size and short duration.…”
mentioning
confidence: 99%
“…(6) Odanacatib inhibits cathepsin K, a cysteine protease produced by osteoclasts that degrades type 1 collagen. Since cathepsin K is relatively specific to osteoclasts, it represents a promising candidate for drug development, and preclinical studies have demonstrated that odanacatib has profound effects on bone resorption with few off-target effects.…”
mentioning
confidence: 99%
See 2 more Smart Citations